Strategi Pemasaran Seven Studio Manna Bengkulu Selatan - Taufik Hidayat; Sulisti Afriani; Rina Trisna Yanti (UNIVED Press, 2022)
Marketing strategy have important role to reach efficacy of effort, therefore marketing area share big in realize plan of[is effort. This matter can be done/conducted, if company wish to maintain and improve sale of service or product which they produce. By doing/conducting applying of accurate marketing strategy pass/through exploiting of opportunity in improving sale, so that position or domicile company in market can be improved or defended. Research type which is used in this research skripsi is with method qualitative. Analysis method which is used in this research is method analyse SWOT ( strength, weaknesses, opportunity, threats ). obtained datas from result of research will be analysed by strength, its weakness, its opportunity, and its threat to applying of strategy marketing of Seven Studio in order to improving buyer enthusiasm. To determine used by marketing strategy formulasi is merger, connective marketing strategy formulasi pass/through matrix of SWOT. Result of research by using analysis of SWOT exist in Seven studio, its of him applying of strategy at the company use Growth Oriented Strategy. From result of research of internal value equal to 0.95 and value of eksternal equal to 1,71. This matter because of, at diagram of cartesius analyse SWOT indicated that by total value of score reside in at first kuadran where the kuadran represent situation that very beneficial. Studio Paradise fruit Seven have many strength and opportunity so that can maintain and exploit existing opportunity at the same time weakness minimization and also overcome various threat exist in paradise fruit studio seven of Bengkulu south.